2022
DOI: 10.3389/fpls.2022.922561
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Regulating Roles of Wheat TaHsfA2-13 in Abiotic Stresses

Abstract: Heat shock transcription factor (Hsf) exists widely in eukaryotes and responds to various abiotic stresses by regulating the expression of downstream transcription factors, functional enzymes, and molecular chaperones. In this study, TaHsfA2-13, a heat shock transcription factor belonging to A2 subclass, was cloned from wheat (Triticum aestivum) and its function was analyzed. TaHsfA2-13 encodes a protein containing 368 amino acids and has the basic characteristics of Hsfs. Multiple sequence alignment analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The experiment was performed with SYBR Green Real-time PCR Master Mix (TaKaRa, Dalian, China) according to the manufacturer's instructions (Bio-Rad, Hercules, CA, USA). Referring to our previous research methods [53], TaRP15 was selected as internal control to normalize the data. The relative expressions of genes were calculated using the average values of 2 −∆∆ct .…”
Section: Gene Expression Analysis Using Rt-qpcrmentioning
confidence: 99%
“…The experiment was performed with SYBR Green Real-time PCR Master Mix (TaKaRa, Dalian, China) according to the manufacturer's instructions (Bio-Rad, Hercules, CA, USA). Referring to our previous research methods [53], TaRP15 was selected as internal control to normalize the data. The relative expressions of genes were calculated using the average values of 2 −∆∆ct .…”
Section: Gene Expression Analysis Using Rt-qpcrmentioning
confidence: 99%
“…Some studies in wheat have shown that Hsf may have the function of regulating wheat to cope with multiple stresses ( Duan et al, 2019 ). Recent studies have shown that the wheat TaHsfA2-13 plays an important role in responding to a variety of abiotic stresses and phytohormones ( Meng et al, 2022 ). Related studies on the identification of HsfA2 in tomato and pepper ( Guo et al, 2014a , 2015 ; Fragkostefanakis et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%